The Influence of Socioeconomic and Nutritional Factors on Reducing Stunting Rates: A Comparative Study of Indonesia and the Philippines - Desya Dillachsyadina Mokke; Sitti Syamsinar; Risnawati, Risnawati (Sean Institute, 2024)
Stunting remains a significant public health issue in developing countries, including Indonesia and the Philippines, where high rates of child malnutrition persist. Stunting impairs physical and cognitive development, limiting the future potential of affected children. This comparative study investigates the influence of socioeconomic and nutritional factors on reducing stunting rates in both countries. A systematic literature review was conducted, focusing on research published between 2010 and 2023, obtained from databases such as Google Scholar and Scopus. The analysis included studies examining the relationship between household income, parental education, nutritional intake, and access to health services, as well as government policy initiatives. Data extraction and thematic analysis were employed to categorize socioeconomic and nutritional determinants of stunting in both countries. The findings suggest that both socioeconomic factors, including parental education and household income, and nutritional factors, such as dietary diversity and breastfeeding practices, significantly influence stunting reduction. Differences in health infrastructure and community-level interventions also contribute to the variations in stunting rates between Indonesia and the Philippines. The study concludes that addressing stunting requires a multifaceted approach, combining socioeconomic improvement, enhanced access to health services, and targeted nutritional interventions. Policies that focus on improving maternal education, community health services, and food security can significantly reduce stunting rates. The findings underscore the importance of coordinated efforts between government, health sectors, and communities to effectively combat stunting and improve child health outcomes in both countries.